Additive Manufacturing of a Special-Shaped Energetic Grain and Its Performance - Yongjin Chen; Shuhong Ba; Hui Ren (Micromachines, 2021)
In order to solve the problems of the complicated forming process, poor adaptability, low safety, and high cost of special-shaped energetic grains, light-curing 3D printing technology was applied to the forming field of energetic grains, and the feasibility of 3D printing (additive manufacturing) complex special-shaped energetic grains was explored. A photocurable resin was developed. A demonstration formula of a 3D printing energetic slurry composed of 41 wt% ultra-fine ammonium perchlorate (AP), 11 wt% modified aluminum (Al), and 48 wt% photocurable resin was fabricated. The special-shaped energetic grains were successfully 3D printed based on light-curing 3D printing technology. The optimal printing parameters were obtained. The microstructure, density, thermal decomposition, combustion performance, and mechanical properties of the printed grain were characterized. The microstructure of the grain shows that the surface of the grain is smooth, the internal structure is dense, and there are no defects. The average density is 1.606 g·cm−3, and the grain has good uniformity and stability. The thermal decomposition of the grain shows that it can be divided into three stages: endothermic, exothermic, and secondary exothermic, and the Al of the grain has a significant catalytic effect on the thermal decomposition of AP. The combustion performance of the grain shows that a uniform flame with a one-way jet is produced, and the average burning rate is 5.11 mm·s−1. The peak pressure of the sample is 45.917 KPa, and the pressurization rate is 94.874 KPa·s−1. The analysis of the mechanical properties shows that the compressive strength is 9.83 MPa and the tensile strength is 8.78 MPa.